The risk of sensorineural hearing impairment in preeclampsia: Risiko Gangguan Pendengaran Sensorineural pada Pasien Preeklamsia - Achmad Taufan; Nuswil Bernolian; Yusuf Efendi; Alba G.E. Bahar (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To determine the risk of sensorineural hearing impairment in preeclampsia patients and to in Obstetric and Gynecology Department in Dr. Mohammad Hoesin Hospital Palembang. Method: An analytic observational case-control study was held in Dr. Mohammad Hoesin Hospital Palembang from January 1st to December 31st 2016. Subjects were obtained through consecutive sampling. Hypothetical tests used were unpaired t-test, Chi-square test and Fisher test for expected deviation standard <5, significance determined based on p-value if p<0.05. Data progressing and analysis were done using SPSS version 17.0 for windows. Results: Characteristics distribution of the subjects were overall homogenous. With the Chi-square test, no significant difference was found in hearing function examination with OAE and tympanometry in both groups (p>0.05). From unpaired t-test, there was no significant difference between mean Air Conducting (AC) and Bone Conducting (BC) of the right ear in severe preeclampsia group and healthy pregnancy group (p=0.340), as well as mean AC and BC of the left ear in severe preeclampsia group and healthy pregnancy group (p=0.059). Based on the Fisher's Exact test, no significant relation was found between severe preeclampsia and sensorineural hearing impairment (p=0.999). Conclusion:There was no significant relation between severe preeclampsia and sensorineural hearing impairment in Obstetric and Gynecology Department in Dr. Mohammad Hoesin Palembang. Keywords: otoacoustic emission, preeclampsia, sensorineural hearing impairment. Abstrak Tujuan: Mengetahui risiko gangguan pendengaran sensorineural pada pasien dengan preeklamsia di Departemen Obstetri dan Ginekologi RSUP Mohammad Hoesin Palembang. Metode: Penelitian analitik observasional dengan disain kasus kontrol pada wanita hamil di RSMH sejak 1 Januari – 31 Desember 2016. Subjek dipilih secara consecutive sampling. Analisis dengan uji t tak berpasangan, Chi-square, dan uji Fisher untuk ekspektasi sd<5, kemaknaan ditentukan berdasarkan (p) jika p<0.05. Proses mengolah dan analisis data ini dilakukan menggunakan SPSS 17.0 for windows. Hasil: Distribusi karakteristik umum subjek secara keseluruhan adalah homogen. Berdasarkan uji Chi Square, tidak didapatkan perbedaan bermakna hasil pemeriksaan fungsi pendengaran dengan OAE dan Timpanometri pada kedua kelompok (p>0,05). Dengan uji T tidak berpasangan, tidak didapatkan perbedaan bermakna rerata Air Conducting (AC) dan Bone Conducting (BC) telinga kanan kelompok PEB dan kelompok hamil normal (p=0,340), begitu juga dengan rerata Air Conducting (AC) dan Bone Conducting (BC) telinga kiri kelompok PEB dan kelompok hamil normal (p=0,059). Berdasarkan uji statistik Fisher, tidak didapatkan hubungan bermakna antara preeklamsia berat dengan gangguan pendengaran sensorineural (p=0,999). Simpulan:Tidak terdapat hubungan yang bermakna antara preeklamsia berat dengan gangguan pendengaran sensorineural berdasarkan pemeriksaan audiometri di Departemen Obstetrik dan Ginekologi RSUP Dr. Mohammad Hoesin Palembang. Kata kunci: gangguan pendengaran sensorineural, otoacoustic emission, preeklamsia